THE EFFECT OF JOB INVOLVEMENT AND EMOTIONAL INTELLIGENCE ON JOB PERFORMANCE (CASE STUDY AT DINAS PERHUBUNGAN, KOMUNIKASI DAN INFORMATIKA SULAWESI UTARA) - Arina, Kevin Thio; Lambey, Linda; Rumokoy, Farlane S. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2017)
Abstract: Job Performance becomes the benchmark for every employee in performing their duties in accordance with the responsibilities given to them and the work that can be achieved. To achieve good performance, employees also need to have a good job involvement also by knowing the involvement of the employees work will be better and able to perform their jobs well and take responsibility for their respective jobs and more satisfied with their jobs. The good performance was also affected by the emotional intelligence of employees in each organization or institution. The ability to control themselves, solve problems, motivate yourself, to overcome frustration, regulate mood, empathy, and the ability to cooperate is an important factor in the emotional intelligence of employees. This research aimed to analyzed The Effect Job Involvement and Emotional Intelligence on Job Performance. This research was analyzed by using multiple regression analysis. In the multiple regression method, regression procedures must to devide the variable into two variables which are dependent and independent variable. Job Involvement (X1) and Emotional Intelligence (X2) as independents variable and Job Performance (Y) as dependent variable. The data was collected from 100 respondents and the data was taken by simple random sampling. This research showed that Job Involvement and Emotional Intelligence simultaneously influence Job Performance, Job Involvement has significant influence on Job Performance partially and Emotional Intelligence has no significant influence on Job Performance partially. Based on the result, Dishubkominfo should concern about job involvement to job performance in term of develop employess skill about job involvement to job performance.Keywords: Job Involvement, Emotional Intelligence, Job Performance.